2019
DOI: 10.1002/kjm2.12010
|View full text |Cite
|
Sign up to set email alerts
|

An overview of microbiome based strategies on anti‐obesity

Abstract: With the significant global obesity epidemic and emerging strong scientific evidence that connected gut microbiota to obesity, intervening obesity by targeting gut microbiota has become a trendy strategy. Particularly the application of probiotics has become remarkably popular because of their expected association with gut microbiota modulation. Although there are many literatures on the effects of probiotics in obese animal models, most of them reported the effects of probiotic bacteria on metabolic indicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 78 publications
0
11
0
1
Order By: Relevance
“…However, whether increased Firmicutes was actually the catalyst for the observed weight gain directly, remains to be seen. The beneficial effects of an ample Bacteroides load displayed in lean individuals, has been attributed to enhanced polysaccharide digesting capabilities with better nutrient metabolism (Chang et al, 2019). However, these findings have not been consistent, as other studies using animal models have demonstrated decreases in Bacteroidetes with no change in Firmicutes, as well as other changes in the bacteria representation, showing no change in metabolic functionality or polysaccharide digesting capabilities (Ejtahed et al, 2016).…”
Section: Microbiome Composition and Obesitymentioning
confidence: 98%
See 1 more Smart Citation
“…However, whether increased Firmicutes was actually the catalyst for the observed weight gain directly, remains to be seen. The beneficial effects of an ample Bacteroides load displayed in lean individuals, has been attributed to enhanced polysaccharide digesting capabilities with better nutrient metabolism (Chang et al, 2019). However, these findings have not been consistent, as other studies using animal models have demonstrated decreases in Bacteroidetes with no change in Firmicutes, as well as other changes in the bacteria representation, showing no change in metabolic functionality or polysaccharide digesting capabilities (Ejtahed et al, 2016).…”
Section: Microbiome Composition and Obesitymentioning
confidence: 98%
“…The world is currently facing an unprecedented increase in the number of overweight and obese individuals (Chang et al, 2019). A staggering 33% of the world's population over the age of 20 is overweight [body mass index (BMI) 25-30 kg/m2] or obese (BMI > 30 kg/m2).…”
Section: Fmt and Obesitymentioning
confidence: 99%
“…In general, the reason for obesity can be stated as an imbalance between energy intake and its expenditure. However, the matter is much more complicated because environmental factors, alongside genetic factors affect the onset of obesity, which in itself is conducive to further dysregulation of energy management [ 18 ••, 58 ]. In the course of obesity, excessive adipose tissue proliferation occurs and related systemic disorders are also observed, including vascular, hormonal (insulin resistance, glucose intolerance), and systemic low-grade inflammation, leading to the development of type 2 diabetes and cardiovascular diseases such as atherosclerosis and hypertension [ 12 ••, 18 ••, 21 , 59 , 60 ].…”
Section: Gut Microbiota and Obesitymentioning
confidence: 99%
“…Other strategies, such as fecal transplantation to alter the gut microbiota, have great potential, as evidenced by animal studies (62,63). However, the impact of fecal transplantation on metabolic health in humans is still emerging (64,65). Although scientific evidence surrounding the microbiome is growing, much of this research to date has been primarily correlational, and more work is needed to understand the mechanisms behind how the gut microbiota influences metabolic health.…”
Section: Studying Neural Mechanisms In Animal Modelsmentioning
confidence: 99%